2012
DOI: 10.1017/jfm.2012.478
|View full text |Cite
|
Sign up to set email alerts
|

On the transition pattern of the oblique detonation structure

Abstract: Oblique detonation waves are simulated to study the evolution of their morphology as gasdynamic and chemical parameters are varied. Although two kinds of transition pattern have previously been observed, specifically an abrupt transition and a smooth one, the determining factors for the transition pattern are still unclear. Numerical results show that the transition pattern is influenced by the inflow Mach number, chemical activation energy and heat release. Despite the fact that these parameters were known to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(68 citation statements)
references
References 18 publications
6
61
0
1
Order By: Relevance
“…For convenience, the coordinate is rotated to the direction along the wedge surface, and simulations are carried out in the region enclosed by the dashed line. Similar to previous numerical studies on oblique detonations (Li, Kailasanath & Oran 1993;Grismer & Powers 1996;Papalexandris 2000;Choi et al 2007;Gui et al 2011;Teng & Jiang 2012;Verreault et al 2013), the present study is also based on the inviscid assumption. In the present study, non-dimensional Euler equations with one-step irreversible Arrhenius kinetic model are used as the governing equations, i.e.…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…For convenience, the coordinate is rotated to the direction along the wedge surface, and simulations are carried out in the region enclosed by the dashed line. Similar to previous numerical studies on oblique detonations (Li, Kailasanath & Oran 1993;Grismer & Powers 1996;Papalexandris 2000;Choi et al 2007;Gui et al 2011;Teng & Jiang 2012;Verreault et al 2013), the present study is also based on the inviscid assumption. In the present study, non-dimensional Euler equations with one-step irreversible Arrhenius kinetic model are used as the governing equations, i.e.…”
Section: Methodsmentioning
confidence: 61%
“…Figueira da Silva & Deshaies (2000) studied the transition distance, and indicated that the smooth transition appeared when the induction time became trivial in total chemical reaction time. Recently, Teng & Jiang (2012) compared results with various chemical and gas dynamic parameters, and demonstrated that the transition type was controlled by the difference of oblique shock and detonation angles.…”
Section: Introductionmentioning
confidence: 99%
“…Generally there are two kinds of transition structures, the abrupt one and the smooth one. The transition structures have been studied and the criterions on the transition type have been proposed [13][14][15]. However, most of previous researchers studied on the static structures, which are assured by the high incident Mach numbers (Ma).…”
Section: Introductionmentioning
confidence: 99%
“…Specific pulse of traditional engines, such as turbo fan and ramjet, decreases dramatically when the flight Mach rises. To resolve this problem, the concept of supersonic combustion is proposed, including the Scramjet [1] and detonation engines [2]. However, the residence time of supersonic combustion is only a few milliseconds, which has the same time scale as the ignition delay time of hydrocarbon fuels.…”
Section: Introductionmentioning
confidence: 99%
“…The ignition characteristics of fuels are more sensitive to the ignition environment such as temperature, pressure and the composition of airflow. The contaminants of H 2 O and CO 2 can change the thermodynamic properties and the composition of test gas mixtures, which may obviously affect the ignition characteristics of fuels.…”
Section: Introductionmentioning
confidence: 99%